2010
DOI: 10.1007/s11104-010-0406-2
|View full text |Cite
|
Sign up to set email alerts
|

An improved way to determine nitrogen fertiliser requirements of sugarcane crops to meet global environmental challenges

Abstract: Nitrogen (N) fertiliser management is increasingly important in sugarcane production as imperatives to reduce environmental impacts of N escalate. In this paper we report testing of a new concept for N management in sugarcane, the N Replacement system. This system relies on soil N cycling to 'buffer' differences in crop N needs and N fertiliser supply to individual crops, and aligns N applications with actual cane production over the longer-term rather than potential production. In 11 experiments, conducted in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
53
1
8

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(66 citation statements)
references
References 35 publications
4
53
1
8
Order By: Relevance
“…However, at the same time this source showed the highest amount of uncountable N in the agro-ecosystem (37 %), hereafter named as N in other compartments -NOC. The NOC comprised N-NO 3 -losses by leaching below 0.60 m in soil profile, N-NH 3 volatilization from the soil or by plant canopy and by N-N 2 O denitrification Thorburn et al, 2011). Basanta et al (2003) evaluated the recovery of N-fertilizer by sugarcane in Brazil during three crops and found that 29 % remained in the soil, 42 % was used by plant and 29 % was lost as NOC, a result very similar to ours.…”
Section: N From Green Harvest Residues Recovery By Sugarcane In Threesupporting
confidence: 76%
See 3 more Smart Citations
“…However, at the same time this source showed the highest amount of uncountable N in the agro-ecosystem (37 %), hereafter named as N in other compartments -NOC. The NOC comprised N-NO 3 -losses by leaching below 0.60 m in soil profile, N-NH 3 volatilization from the soil or by plant canopy and by N-N 2 O denitrification Thorburn et al, 2011). Basanta et al (2003) evaluated the recovery of N-fertilizer by sugarcane in Brazil during three crops and found that 29 % remained in the soil, 42 % was used by plant and 29 % was lost as NOC, a result very similar to ours.…”
Section: N From Green Harvest Residues Recovery By Sugarcane In Threesupporting
confidence: 76%
“…The crop residues incorporated into the soil during sugarcane pre planting operation were low effective to supply N for sugarcane nutrition (Table 2), but may have an important role for sustainability in tropical agro-ecosystems due to its contribution in supplying organic C, N and other nutrients for the soil organic matter in long-term (Thorburn et al, 2011). Indeed, the fate of above and below ground residues from last crop after 5 years (2005 to 2009) was in the soil (45 % and 59 % of total N present in the above and below ground of sugarcane residues, respectively), highlighting the importance of these materials in providing N to the soil (Figure 4).…”
Section: N From Green Harvest Residues Recovery By Sugarcane In Threementioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, N fertilization management is a challenge beyond the replacement of crop requirements and must take into account the agronomic and environmental impacts of mineral fertilizers and crop residues on the agroecosystems, as well as in C, N, and other nutrient balances in soil-plant-atmosphere (Dourado Neto et al, 2010;Fortes et al, 2011;Thorburn et al, 2011).…”
Section: Introductionmentioning
confidence: 99%